Synthesis and study of the cancer cell growth inhibitory properties of α-, γ-tocopheryl and γ-tocotrienyl 2-phenylselenyl succinates - Vraka, Panayiota S.; Rikkou, Maria P.; Drouza, Chryssoula (My University, 2006)
Vitamin E succinate selenium-conjugated molecules were synthesized and their apoptogenic properties were evaluated. 4-Methyl-2-phenylselenyl succinate (4) was prepared by the reaction of sodium benzeneselenolate with 2-bromosuccinic anhydrite in methanol solution. The methyl ester was converted to the acid (5) by hydrolysis with aqueous hydrochloric acid. Reaction of the 2-phenylselenyl succinic anhydrite (6) with α-tocopherol (1a), γ-tocopherol (1c), and γ-tocotrienol (2c) in acidic conditions gave the respective esters. The free radical scavenging properties of α-tocopheryl-2-phenylselenyl succinate (7), γ-tocopheryl-2- phenylselenyl succinate (8), and γ-tocotrienyl-2-phenylselenyl succinate (9) were evaluated in comparison with those of α-tocopheryl succinate (10), γ-tocopheryl succinate (11), and γ-tocotrienyl succinate (12), respectively, and the free tocopherols and γ-tocotrienol. Compounds 7-9 induced a statistically significant decrease in prostate cancer cell viability compared to 10-12, respectively, or 5, exhibiting features of apoptotic cell death and associated with caspase-3 activation. These data show that structural modifications of vitamin E components by 5 enhance their apoptogenic properties in cancer cells
Keywords: Apoptosis; Cancer cells; Tumors--Growth; Canser; Drugs; Enzyme activation; Apoptosis; Human beings